2018
DOI: 10.1667/rr14976.1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Abnormalities in Human Lymphocytes after Computed Tomography Scan Procedure

Abstract: The incidence of chromosomal abnormalities and cancer risk correlates well with the radiation dose after exposure to moderate- to high-dose ionizing radiation. However, the biological effects and health risks at less than 100 mGy, e.g., from computed tomography (CT) have not been ascertained. To investigate the biological effects of low-dose exposure from a CT procedure, we examined chromosomal aberrations, dicentric and ring chromosomes (dic+ring), in peripheral blood lymphocytes (PBLs), using FISH assays wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…Even though the mean values of all patients as a group for all three endpoints tested show increased yields relative to baseline following medical exposure, our results demonstrate that only the γ-H2AX biomarker enables detection of statistically The present observations agree with cytogenetic studies carried out in patients exposed to low IR doses. Particularly, according some studies the numbers of dicentric and ring chromosomes were significantly increased after a CT scan in patients (13,19,(27)(28)(29). In our study, after the cardiac interventional procedures, which have resulted in a mean dose of about 14 mSv a total of 48.000 cells have been analyzed.…”
Section: Discussionmentioning
confidence: 67%
“…Even though the mean values of all patients as a group for all three endpoints tested show increased yields relative to baseline following medical exposure, our results demonstrate that only the γ-H2AX biomarker enables detection of statistically The present observations agree with cytogenetic studies carried out in patients exposed to low IR doses. Particularly, according some studies the numbers of dicentric and ring chromosomes were significantly increased after a CT scan in patients (13,19,(27)(28)(29). In our study, after the cardiac interventional procedures, which have resulted in a mean dose of about 14 mSv a total of 48.000 cells have been analyzed.…”
Section: Discussionmentioning
confidence: 67%
“…Although the characteristics of participants who underwent LD CT and/or SD CT were not significantly different, there was a slight difference in the number of CAs before CT. Consequently, on the basis of observations reported by Shi et al (28), CT the CA number was 7.8 (IQR, 4.4211.0) and 9.2 (IQR, 6.5213.9), respectively (P = .009).…”
Section: Semiautomatic Counting Of Chromosome Aberrationsmentioning
confidence: 67%
“…g-H2AX is a marker of DNA double-strand break; CAs reflect both the damage from radiation exposure and the accuracy of DNA repair. Individual variations in the response to DNA damage (18,28) may explain the absence of a correlation between the number of g-H2AX foci and CAs after CT and the dose-length product and the degree of DNA damage.…”
Section: Semiautomatic Counting Of Chromosome Aberrationsmentioning
confidence: 99%
“…Since this reduction at 24 hours in the γ-H2AX score was not observed in the very-low-dose group, we could not clearly state that continuous low-dose radiation decreased the DSB, but it was suggested that DSBs were efficiently repaired after 6 hours in the cells cultured on the radiation-emitting sheets. When DSB and chromosome damage are evaluated immediately or shortly after low-dose (<100 mGy) radiation, increases in the indices may be observed, 22,23 but the damage may be efficiently repaired thereafter or damaged cells may be eliminated by apoptosis and replaced with new cells by the effect of low-dose radiation. Overall, low-dose radiation may enhance the DNA repair capacity and contribute to repair of DSB following subsequent exposure to a high dose of radiation.…”
Section: Discussionmentioning
confidence: 99%